2015
DOI: 10.7182/pit2015550
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of, Beliefs About, and Perceived Barriers to Organ and Tissue Donation in Serbian, Macedonian, and Greek Orthodox Communities in Australia

Abstract: Clear barriers to discussing and making an informed decision about organ and tissue donation were identified. Knowledge of processes and procedures was low and discussion about death (and organ and tissue donation) with family members and loved ones was considered taboo. Despite these barriers, all 3 communities expressed a desire for more information and engagement. Of particular interest were the perspectives of 3 types of "experts": medical, religious, and other community members (who had experience with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…According to the study by Phillipson et al (12) 3 types of “experts”: medical, religious, and other community members (who have had experience with the organ and tissue donation system, and testimonies from people who have been personally involved in both the donation and receipt of organs and tissues) are important in improving the donation process. This study also indicates the necessity of further active engagement by health workers, especially those included in the transplantation process, in order to raise the level of general knowledge about the necessity of organ donation, but also inclusion of educational workers in the educational process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study by Phillipson et al (12) 3 types of “experts”: medical, religious, and other community members (who have had experience with the organ and tissue donation system, and testimonies from people who have been personally involved in both the donation and receipt of organs and tissues) are important in improving the donation process. This study also indicates the necessity of further active engagement by health workers, especially those included in the transplantation process, in order to raise the level of general knowledge about the necessity of organ donation, but also inclusion of educational workers in the educational process.…”
Section: Discussionmentioning
confidence: 99%
“…Useful information obtained from medical experts regarding organ donation, as well as responses from religious communities and local religious leaders, together with testimonies from people who had been personally involved in both the donation and receipt of organs and tissues, can lead to increased interest in and influence on organ donation (11, 12). Therefore, it is essential to learn about the attitude of social groups that might have a strong influence on public opinion, such as health-care professionals and school staff (13-15).…”
Section: Introductionmentioning
confidence: 99%
“…Such fears are caused by hospitals ill‐equipped to undertake organ transplantation in general and surgery in particular. While the first fear requires improvements to the competence of health officials and quality of medical equipment and procedures , the second problem can be addressed by improving access to information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jones‐Riffell and Stoeckle () found that increased knowledge is the most important factor in forming attitudes towards OD. A recent study by Phillipson, Larsen‐Truong, Pitts, and Nonu () found that the awareness about the procedures and process is low, and it is considered as a barrier towards OD. Hence, we posit:H1 Perceived awareness about OD is positively related to ODA.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Religion plays a very important role than it is believed to be (Oliver, Woywodt, Ahmed, & Saif, 2011;Sprung, Maia, & Bulow, 2007). Religious communities and leaders can enhance OD (Bener, El-Shoubaki, & Al-Maslamani, 2008;Phillipson et al, 2015). Religious beliefs is an important factor influencing one's thought when considering OD (Bresnahan et al, 2007) and an important reason individuals cite when consenting to donate organs (Morgan et al, 2008).…”
Section: Religiositymentioning
confidence: 99%